2015
DOI: 10.1161/circulationaha.114.013760
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke in Chronic Heart Failure Patients Without Atrial Fibrillation

Abstract: Background— Our aim was to describe the incidence and predictors of stroke in patients who have heart failure without atrial fibrillation (AF). Methods and Results— We pooled 2 contemporary heart failure trials, the Controlled Rosuvastatin in Multinational Trial Heart Failure (CORONA) and the Gruppo Italiano per lo Studio della Sopravvivenza nell’Insufficienza cardiaca-Heart Failure trial (GISSI-HF). Of the 9585 total patients, 6054 did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 31 publications
3
38
2
Order By: Relevance
“…[25] In our study, although the risk of TE was lower among HF patients in sinus rhythm than those with AF, the annual incidence was 2.91% per year, markedly higher than the reported incidence of 1.45 per 1000 persons per year in the general population. [31] Nevertheless, the risk of TE is not the same among all HF patients in sinus rhythm.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…[25] In our study, although the risk of TE was lower among HF patients in sinus rhythm than those with AF, the annual incidence was 2.91% per year, markedly higher than the reported incidence of 1.45 per 1000 persons per year in the general population. [31] Nevertheless, the risk of TE is not the same among all HF patients in sinus rhythm.…”
Section: Discussioncontrasting
confidence: 51%
“…In a pooled analysis of two clinical trials largely consisting of patients with chronic HFREF, Abdul-Rahim and colleagues have shown that age, previous stroke, New York Heart Association class, diabetes mellitus treated with insulin and body mass index predicted stroke in HF patients without AF. [5] We did not include New York Heart Association class or body mass index in our analysis, as both parameters are dynamic and particularly inaccurate in patients with new-onset HF. [5] Furthermore, we did not find prescription of insulin predictive of TE, in contrast to the findings by Abdul-Rhaim et al[5] This is not surprising, as prescription of insulin in real-life situation can be affected by many factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sub-group analysis of the WARCEF Trial, the risk of new ischemic cerebrovascular event has been found to be high in patients with EF <15% compared to other HF-REF patients (86). In an analysis performed recently, the risk of stroke was shown to be 60% higher in HF-REF patients in sinus rhythm with NYHA Class III-IV symptoms than patients with NYHA Class II symptoms (85). Hence, theoretically, anticoagulant therapy may be beneficial in HF-REF patients with low EF and high NYHA class.…”
Section: Should Warfarin Be Administered In Case Of Severe Ventriculamentioning
confidence: 99%
“…Therefore, warfarin therapy has no benefit in patients with HF-REF in sinus rhythm (patients should be closely monitored regarding paroxysmal AF). On the other hand, in a study examining the recent CORONA and GISSI-HF collective dataset, it was suggested that a subgroup could be determined in which anticoagulant treatment might have been beneficial even if there was no AF in the high-risk patients with HF-REF (85). This expectation is being tested in the ongoing COMMANDER-HF Trial regarding the possible positive effect of NOAC therapy (69).…”
Section: Does Warfarin Therapy Have a Place In Patients With Hf In Simentioning
confidence: 99%